DVAITA VEDANTA DALAM TEKS LONTAR BHUWANA MAHBAH - Mery Ambarnuari (Sanjiwani: Jurnal Filsafat, 2019)
The development and dissemination of Hindu teachings makes the Vedas Holy Library A lot of text passages, one of which is the regional texts written by citing the teachings in the Vedic Sacred Library. The text of Bhuwana Mahbah Lontar is one of them. The text discussing the creation and preservation of the universe contains teachings that correspond to the dualist Dvaita Vedanta, which, among others, created the universe different from its creations but the creation is still in control God as the ultimate reality.